2020
DOI: 10.1371/journal.pone.0235908
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive user interface design and analysis using emotion recognition through facial expressions and body posture from an RGB-D sensor

Abstract: This work presents the design and analysis of an Adaptive User Interface (AUI) for a desktop application that uses a novel solution for the recognition of the emotional state of a user through both facial expressions and body posture from an RGB-D sensor. Six basic emotions are recognized through facial expressions in addition to the physiological state, which is recognized through the body posture. The facial expressions and body posture are acquired in real-time from a Kinect sensor. A scoring system is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Recent research has explored the applications of emotion recognition and eye-tracking in web interaction design. These studies have demonstrated how the real-time detection of user emotions can lead to adaptive interfaces that tailor content based on emotional feedback [7]. Additionally, eyetracking data has been used to identify areas of interest on web pages, allowing designers to optimize the placement of critical elements [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent research has explored the applications of emotion recognition and eye-tracking in web interaction design. These studies have demonstrated how the real-time detection of user emotions can lead to adaptive interfaces that tailor content based on emotional feedback [7]. Additionally, eyetracking data has been used to identify areas of interest on web pages, allowing designers to optimize the placement of critical elements [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This summary shown in Table I, encapsulates the cross-validation method used, the resolution to which images were resized, and the normalization parameters for RGB channels [10] applied to the AffectNet dataset. These characteristics are crucial for understanding the dataset's structure and preparing it for effective model training and evaluation in computer vision tasks.…”
Section: Data Sectionmentioning
confidence: 99%
“…The application of emotion recognition methods in UX evaluation, however, has not always been so straightforward. As UX has become an essential process to measure the user's satisfaction and usability, for which emotion can act as a key aspect for evaluating practical applications or software products [3].…”
Section: Introductionmentioning
confidence: 99%